الجريدة الرسمية العدد 44 - رئيس مجلس الوزراء (المطابع الاميرية, 2025)
قرارات رئيس مجلس الوزراء : قرار رقم 2505 لسنة 2024 -- قرار رقم 3112 لسنة 2024 -- قرار رقم 3113 لسنة 2024 -- قرار رقم 3370 لسنة 2024 -- قرار رقم 3371 لسنة 2024 -- قرار رقم 3372 لسنة 2024 -- قرار رقم 3373 لسنة 2024 -- قرار رقم 3374 لسنة 2024 -- قرار رقم 3375 لسنة 2024 -- قرار رقم 3376 لسنة 2024 -- قرار رقم 3377لسنة 2024 --